Hubungan Usia dengan Tingkat Kecamasan pada Pasien Bedah Elektif Dewasa - Harits Abdurahman Anwar; Septian Mixrova Sebayang; Asmat Burhan (Jurnal Keperawatan Malang, 2024)
Background: Every patient has different views and reactions to surgery,one of which is experiencing anxiety. Anxiety can be influenced by several characteristics, including age, gender, education, work situation, and marital status. The purpose of this study was to determine whether there is a relationship between patient age and anxiety level in elective surgical patients at Goeteng Taroenadibrata Hospital. Methods: This study used an analytical correlation research method with a quantitative approach. The sampling technique used Consecutive Sampling and 79 pre-anesthesia respondents were sampled for this study. The testused in this study is Kendall Tau Result: The results of the correlation test obtained a significance value for the level of anxiety with a P-value of 0.002 <0.05, and the majority of respondents experienced a moderate level of anxiety with a total of 42 respondents. Implications: From the results of the study, it can be seen that there is a correlation between age and anxiety levels of adult surgical patients at Goeteng Taroenadibrata Purbalingga Hospital. The findings of this study, it is expected to improve pre-operative care for patients in emergencies such as providing preoperative education to reduce anxiety in surgery patients. Keywords: Age;Anxiety;Surgery